AVALIAÇÃO DAS CONDIÇÕES HIGIÊNICO-SANITÁRIAS DA ÁGUA DAS PRAIAS DO MUNICÍPIO DE SÃO LUÍS-MA - Silva, Viviane Correa da (2006)
The aim of this work was to evaluate the hygienic and sanitary conditions of the beaches of the São Luís municipality, using as an indicator the Enterococcus. Two distinct periods were studied: rainy and drought seasons. The samplings were performed fortnightly during the rainy season and weekly at dry season. The pH was measured at the point of the water sampling area and the laboratorial microbiologic analyses were performed by using the method of multiple tubes, as preconized by the American Public Health Association APHA (1995). The pH was found at the normal standard level, between 7 and 8, for the all examined beaches. High counts of Enterococcus, between 102 and 103 MPN/100 mL, were found to the drought season, and reaching 105 MPN/100 mL in the rainy season. It was concluded that the beaches of the Ponta da Areia and Calhau were characterized as improper for swimming at the examined periods, while the Olho d Água and Araçagi beaches were suitable.